Barack Obama : United States President : updated and expanded! - Edwards, Roberta; Call, Ken (New York : Grosset & Dunlap, 2009)
A short biography of Barack Obama, the first African- American president-elect.
Previously published as: Barack Obama : an American story.
NC 680
Keywords: Obama, Barack -- Juvenile literature; United States. -- Congress. -- Senate -- Biography -- Juvenile literature; Presidential candidates -- United States -- Biography -- Juvenile literature; Presidents -- United States -- Election -- 2008 -- Juvenile literature; Legislators -- United States -- Biography -- Juvenile literature; African American legislators -- Biography -- Juvenile literature; African Americans -- Biography -- Juvenile literature; Racially mixed people -- United States -- Biography -- Juvenile literature